MOTIVATIONAL FACTORS OF EMPLOYEES IN THE EDUCATIONAL SECTOR IN SURABAYA CITY - Wibisono, Alexander Hiro; Utami, Christina Whidya (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study explores the key factors motivating teachers in Surabaya City by distinguishing between internal and external dimensions of motivation. Using motivation theory as its foundation, the research seeks to identify the dominant drivers influencing teacher performance. Data were collected from 100 teachers across primary, junior high, and senior high schools through an online questionnaire, following a pre-survey using focus group discussions. Exploratory factor analysis revealed two main motivational factors: professional growth and recognition, and organizational support. Career advancement emerged as the strongest motivator, supported by training, incentives, and peer recognition, while adequate facilities and acknowledgment from school leaders also played a significant role. Overall, the study highlights the critical role of career development, recognition, and institutional support in strengthening teacher motivation, offering practical insights for education human resource management despite its geographic limitations.